Beta-Blocker-Related Atrioventricular Conduction Disorders—A Single Tertiary Referral Center Experience - Dragoș Traian Marius Marcu; Cristina Andreea Adam; Dan-Mihai Dorobanțu; Delia Lidia Șalaru; Radu Andy Sascău; Mircea Ovanez Balasanian; Liviu Macovei; Cătălina Arsenescu-Georgescu; Cristian Stătescu (Medicina, 2022)
Background and Objectives: Drug-related bradyarrhythmia is a well-documented major adverse event among beta-blocker users and a potential cause for hospitalization or additional interventions. Whether beta-blocker use is associated with specific bradyarrhythmia presentations, and how this relates to other predisposing factors, is not well known. We aim to evaluate the association between beta-blocker use and the type of atrioventricular (AV) conduction disorder in patients with symptomatic bradycardia. Materials and Methods: We conducted a retrospective cohort study on 596 patients with a primary diagnosis of symptomatic bradyarrhythmia admitted to a single tertiary referral center. Of the cases analyzed, 253 patients were on beta-blocker treatment at presentation and 343 had no bradycardic treatment. We analyzed demographics, clinical and paraclinical parameters in relation to the identified AV conduction disorder. A multivariate regression analysis was performed to explore factors associated with beta-blocker use. Results: Of the 596 patients (mean age 73.9 ± 8.8 years, 49.2% male), 261 (43.8%) had a third-degree AV block, 92 (15.4%) had a second-degree AV block, 128 (21.5%) had slow atrial fibrillation, 93 (15.6%) had sick sinus syndrome and 21 (3.5%) had sinus bradycardia/sinus pauses. Beta-blocker use was associated with the female gender (p < 0.001), emergency admission (p < 0.001), dilated cardiomyopathy (p = 0.003), the lower left ventricular ejection fraction (p = 0.02), mitral stenosis (p = 0.009), chronic kidney disease (p = 0.02), higher potassium levels (p = 0.04) and QRS duration > 120 ms (p = 0.02). Slow atrial fibrillation (OR = 4.2, p < 0.001), sick sinus syndrome (OR = 2.8, p = 0.001) and sinus bradycardia/pauses (OR = 32.9, p < 0.001) were more likely to be associated with beta-blocker use compared to the most common presentation (third-degree AV block), after adjusting for other patient characteristics. Conclusions: Beta-blocker use is more likely to be associated with slow atrial fibrillation, sick sinus syndrome and sinus bradycardia/pauses, compared to a second- or third-degree AV block, after adjusting for other patient factors such as gender, admission type, ECG, comorbidities, cardiac function and lab testing.